Nutrient Management in Hydroponic Systems for Urban and Peri-Urban Agriculture - Jadhav, A. B. (Journal of Agricultural Extension Management, 2023)
Soil based agriculture systems in urban and peri-urban areas or around metro cities is facing various challenges such as rapid urbanization, industrialization, natural disaster, declining soil fertility, mineral mining and sewage water based polluted leafy vegetables etc. which are creating lot many problems. In the new era, soilless cultivation is gaining popularity all over the world and India because of efficient use of the water, fertilizers and other resources for quality vegetable production in urban and peri-urban areas. In this article historical background of soilless culture and various types of soilless culture systems their advantages and limitations are discussed. Among factors affecting soilless production systems, the nutrient solution is considered to be one of the most important determining factors of crop yield and quality. Plant nutrients, classification, their functions and essentiality for plants along with plant usable forms and critical nutrient concentration are thoroughly discussed in the article. The concept of pH of the nutrient solution and its effect on nutrient availability; relation between electrical conductivity and osmotic potential along with its effects on nutrient uptake are discussed in the article. Oxygenation in the nutrient solution is also important for root growth and overall plant growth; factors affecting nutrient solutions behaviour are also reported, emphasizing temperature; formulation and preparation of nutrient solutions considering different fertilizer sources are described as well.